Legal Organization of the Accusation Against the Head of the Parliament - Karrar Hadi Sahar Ghilan (International Journal of Law and Society, 2025)
One of the most important legal challenges is accusing the Head of Parliament, especially in light of the Republic of Iraq's 2005 Constitution. This fact results from the fact that, because it targets the accusing organization, it is the only constitution administered democratically. Internal regulations will be utilized to establish the legislative authority as he is the head of it, provided that they do not conflict with the provisions of the constitution. The study's goals of identifying, discussing, and resolving the most significant legal concerns in this case—drawing on the Iraqi constitution and the laws that attempt to call all matters relevant to the subject of accusation—thus highlight the study's significance. “especially in light of what the Iraqi constitutional legislator has neglected to address the questioning or dismissal of the Head of the Parliament and the reasons that require that.